2008
DOI: 10.1590/s0103-507x2008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Insuficiência adrenal relativa no choque séptico: comparação da resposta ao tratamento com hidrocortisona em pacientes diagnosticados através de dosagem única do cortisol plasmático versus teste da corticotropina

Abstract: 25 mg/dL. No grupo 2, os pacientes com D cortisol < 9 mg/dL tiveram tempo de infusão de noradrenalina menor (3 dias) comparado aos pacientes com D cortisol > 9 mg/dL (6 dias). CONCLUSÕES: O teste da corticotropina com 1 mg foi mais eficiente que a dosagem única do cortisol plasmático < 25 mg/dL, para o diagnóstico da insuficiência adrenal relativa no paciente com choque séptico.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Of these 185, 15 were initially classified as randomized clinical trials. (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) These 15 original articles were analyzed regarding concealment of allocation, and six articles (17,(19)(20)(21)(22)(23) (40%) ranked as A, other six articles (10,(13)(14)(15)(16)18) (40%) ranked as B, two articles (11,12) (13.3%) as C and one article (9) (6.7%) that was not a randomized clinical trial was ranked as D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 185, 15 were initially classified as randomized clinical trials. (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) These 15 original articles were analyzed regarding concealment of allocation, and six articles (17,(19)(20)(21)(22)(23) (40%) ranked as A, other six articles (10,(13)(14)(15)(16)18) (40%) ranked as B, two articles (11,12) (13.3%) as C and one article (9) (6.7%) that was not a randomized clinical trial was ranked as D.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the quality assessment disclosed that 7% (1/13) of the articles were of good quality (22) (Table 1). Score distribution on the quality scale was: zero for 8 (57.2%) original articles (10)(11)(12)(13)(14)(15)(16)18) 2 points for 5 (35.7%) (17,(19)(20)(21)23) and 4 points for one (7.1%) original article that presented good methodological quality. (22) The assessment of the secondary variables of all original articles showed that: 110 (59.5%) original articles described submitting the project to a Committee of Ethics in Research, 53 (28.6%) described use of informed consent, 19 (10.3%) described sample size calculation, 146 (78.9%) described the variables analyzed, 118 (63.8%) described inclusion criteria, 90 (48.6%) described exclusion criteria and in only 3 (1.6%) was there a description of the funding source.…”
Section: Resultsmentioning
confidence: 99%
“…(7-9,11,19,24-27) However, this finding is still controversial, especially in the aftermath of the publication of the CORTICUS study, which raised doubts about the utility of the ACTH test and even the beneficial effect of low-dose hydrocortisone in severe sepsis. (28) Although CIRCI is recognized as a dysfunction, (5,15) different trials have shown different results about the treatment of this dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…( 2 , 16 , 17 ) Baseline cortisol levels alone could also be used to help identify CIRCI; however, no trials could identify a baseline cortisol cutoff point that could be used to diagnose CIRCI or guide therapy. ( 2 , 18 , 19 ) In the course of severe disease, low levels of cortisol-binding proteins and hypoalbuminemia may lower total cortisol levels and responses to ACTH independently of free cortisol levels and in the absence of CIRCI. ( 20 - 22 ) However, the measurement of free cortisol (biologically active) in serum or saliva is not widely available and requires further studies in critical care patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation